Predicting the Bankruptcy of Cement Companies in Bangladesh: A Study on Dhaka Stock Exchange - Hoque, Emranul; Hossain, Tarik; Saha, Trina (International Journal of Business, Economics and Management, 2022)
The financial status of a company can be measured and predicted using a variety of tools, techniques, and models like ratio analysis, vertical and horizontal analysis, etc. The objective of this study is to identify the bankruptcy position of Bangladeshi-listed cement companies. The Altman Z-Score model has been used here to assess the intensity of insolvency of Bangladeshi cement businesses with listings on Dhaka Stock Exchange (DSE) considering financial information from 2018 to 2021 using Altman Z-Score model. The data has been analyzed using Statistical Package for Social Sciences (version 28.0.1.1) and also Microsoft excel. DSE currently lists seven (07) cement companies. According to the research, Heidelberg Cement Limited and Lafarge Holcim Bangladesh Limited are in the secure region having the maximum Z value of 33.47 and the minimum Z value is 3.17. Confidence Cement Limited, Meghna Cement Limited and Crown Cement Limited in 2021 are in the grey region having the maximum Z value of 2.71 and the minimum Z value of 1.82. Aramit Cement Limited, Crown Cement Limited, and Premier Cement Mills Limited are in the bankrupt region having the Z value of less than 1.80. These three companies must outperform in sales with the improvement in operational costs to overcome bankruptcy. We found a positive correlation between all of the five independent variables and the dependent variable (Z Score).